Learning, teaching, and community : contributions of situated and participatory approaches to educational innovation - Pease-Alvarez, Lucinda; Schecter, Sandra R. (L. Erlbaum, 2005)
This volume explores how participatory and situated approaches to learning can contribute to educational innovation. The contributors' examinations of educational programming and engagements provide insights into how educators, youth, families, and community members understand and enact their commitments to diversity and equitable access.